Program Pelatihan Pembuatan Sabun Cair Pencuci Piring untuk Ibu-Ibu PKK di Kelurahan Sungai Jering, Kecamatan Kuantan Tengah, Kabupaten Kuantan Singingi - Rahayuningsih, Jumriana; Yuhelman, Nofri; Irfandi, Irfandi; Murwindra, Rosa; Musdansi, Dwi Putri (Jurnal Pengabdian Cendikia Nusantara, 2024)
The increasing need for liquid dish soap in the community encourages the need for skills to make this product independently. This community service aims to provide knowledge and skills in making liquid dish soap to PKK mothers in Sungai Jering Village, Kuantan Tengah District, Kuantan Singingi. This activity was organized by FTK UNIKS Chemistry Education Lecturers with discussion methods, material exposure, knowledge sharing, and hands-on practice. The material includes an introduction to the basic ingredients of soap, including surfactants as the main component of stain lifters, as well as the process of making liquid soap. The results of the activity showed that the participants succeeded in producing liquid dish soap according to the method taught. This training not only improved participants' skills, but also opened up opportunities to save household expenses and potentially improve the family economy through independent production. This activity is effective in transferring knowledge and practical skills, and has the potential to have a positive impact on the economic welfare of participants.